Difficulties in the dialogue in elementary classroom - Álvarez Álvarez, Carmen (Didáctica. Lengua y Literatura, 2012)
The purpose of this paper is to review the difficulties posed by dialogic teaching methods in primary education from the point of view of regular dynamics in the classroom, to provide a realistic look at the common problems they face, teachers at this level when talking to the students. The article raises the relevance of methodologies that give the word to students in education, showing the interest that is currently in pedagogy, given its many advantages, which shows the importance of further research on them. Following is the model followed by data collection, the ethnographic approach and its potential in the study of these dynamics of the classroom to allow the researcher to know the reality of teaching from the heart of it: in the classroom. Specifically, this is a case study. In the bulk of the article speaks of the difficulties that often occur in the classroom when it comes to bringing a dynamic oral student. We present the main difficulties encountered in the Primary Education classroom under study, which are classified in three categories: pedagogical, sociological and psychological and realize them to address the specific problem in detail and showing the collected episodes throughout the research highlights the difficulties reported. Finally it makes some interesting conclusions about this method of teaching. The sense of this approach to the difficulties that can arise when attempting a conversational methodology far from being negative or contrary to it, contributes to reasonably assert, and far from triumphalism attitudes frequent as naive or well-meaning attitudes.
Keywords: Dialogue; classroom communication; teaching methodology; classroom situation; elementary school children.